OPTIMIZATION OF THE MOTOR ACTIVITY OF STUDENTS SUFFERING FROM DIABETES MELLITUS DURING PHYSICAL EDUCATION CLASSES - Soslan Adyrkhaiev (European Scientific Journal, ESJ, 2014)
The article is devoted to the actual problem of optimization of motor activity of students with different nosologies, formation of stable motivation to systematically perform physical exercises, attracting to the healthy lifestyle during the entire period of study at the university and in further professional activity. The author offers a new technique of teaching motor actions and increase of physical activity for students suffering form diabetes, that is an innovative approach to physical education and sports for youth with different nosologies.